Odonata (Insecta) como indicador de la calidad ambiental en humedales de montaña neotropicales - López-Díaz, Juan Antonio; Gómez, Benigno; González-Soriano, Enrique; Gómez-Tolosa, María (Instituto de Ecología, A.C., 2021)
In order to evaluate the diversity of the Odonata order and relate it to environmental quality, in San Cristobal de Las Casas (Chiapas) four wetlands were chosen according to their accessibility and permissibility. For the environmental typology, among other characteristics, the visual quality was considered, estimated through the Index of the State of Conservation of Wetlands (IECH). Systematic monthly collections of adult odonates were carried out between July 2014 and June 2015. A total of 14 species, distributed in five families and 10 genera were found. The genus Argia was the richest, while Ischnura denticollis and Enallagma rua represented the dominant species. Las Cañadas, a wetland with suboptimal visual quality, presented the greatest diversity of dragonflies by integrating a lotic environment. As one of the parameters evaluated in the visual quality, the degree of alteration of the aquatic vegetation was very important in the differences found in the diversity and abundance of Odonata in the four wetlands. Maria Eugenia and La Kisst classified as environments with optimal and regular visual quality, respectively, obtained the greatest similarity in their odonatofauna related to the different life forms of their aquatic vegetation and for the equivalent size of these two wetlands.